PERILAKU DAN KEPUASAN PELANGGAN BANK MUAMALAT INDONESIA CABANG SURABAYA DENGAN MENGGUNAKAN ANALISIS REGRESI LOGISTIK - Suparto Suparto (Jurnal Keuangan dan Perbankan, 2008)
In this research, it will be known relation between identity variable and customerbehavior that influence their satisfaction level to BMI services. From logistic regression analysis,has been conclude that males trend felt satisfied 2.503 times than female on BMI services. Thecustomer who have occupation as public officer or in the army seems felt satisfied 1.883 times,and the customer who have occupation in private company, 0.480 times if were comparedwith the other. The customer who less than 1 year seems have probability to feel satisfied 0.246and the customer who between 1-2 year, 2.333 times compared customer who more than 2years. The customer who become an BMI customer as himself/herself felt satisfied 1.919 times,with family recommendation 0.96 times, and want as himself, with friend recommendation0.1 times if are compared with the other.